Homary i homarce w świecie antycznym - Tadajczyk, Konrad; Witczak, Krzysztof Tomasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Konrad Tadajczyk, Krzysztof Tomasz Witczak, Homary i homarce w świecie antycznym (European and Norway lobsters in the ancient world). The article describes the Greek and Latin names for ‘European lobster, Homarus gammarus L.’ and ‘Norway lobster, Nephrops norvegicus L.’. The present authors suggest that the European lobster was called λέων in Greek and leō in Latin. The Greek term ἀστακός (hence Lat. astacus) referred exclusively to the Norway lobster.